2016
DOI: 10.3892/etm.2016.3063
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated TGF-β3, CTGF and TIMP1 gene transduction as a gene therapy for intervertebral disc degeneration in an in vivo rabbit model

Abstract: The present study examined the effects of transforming growth factor (TGF)-β3, connective tissue growth factor (CTGF) and tissue inhibitor of metalloproteinase 1 (TIMP1) gene transduction, using a lentiviral vector, on rabbit intervertebral disc degeneration , with the intention of investigating their potential use in gene therapy. A model of lumbar intervertebral disc degeneration was created by needle puncture into the annulus fibrosus of 15 New Zealand white rabbits. Empty lentivirus or recombinant lentivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Cell therapy, such as mesenchymal stem cells (MSCs) in matrix constructs, has been identified as a promising therapeutic strategy to promote regeneration; however, limitations remain regarding cell retention and viability in the degenerate IVD . Pro‐anabolic gene therapy‐based approaches have been proposed including viral transfection of SOX9, which resulted in increases in matrix synthesis (collagen II) in degenerate rabbit NP . However, the use of viral vectors for gene delivery poses concerns of insertional mutagenesis and unwarranted immune responses .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell therapy, such as mesenchymal stem cells (MSCs) in matrix constructs, has been identified as a promising therapeutic strategy to promote regeneration; however, limitations remain regarding cell retention and viability in the degenerate IVD . Pro‐anabolic gene therapy‐based approaches have been proposed including viral transfection of SOX9, which resulted in increases in matrix synthesis (collagen II) in degenerate rabbit NP . However, the use of viral vectors for gene delivery poses concerns of insertional mutagenesis and unwarranted immune responses .…”
mentioning
confidence: 99%
“…[16][17][18][19][20] Proanabolic gene therapy-based approaches have been proposed including viral transfection of SOX9, which resulted in increases in matrix synthesis (collagen II) in degenerate rabbit NP. [21][22][23] However, the use of viral vectors for gene delivery poses concerns of insertional mutagenesis and unwarranted immune responses. [24][25][26] Nonviral plasmid-based vector systems eliminate much of the risk associated with viral vectors and have been used successfully in conjunction with novel tissuenanotransfection for rescue of mice skin tissue under ischemic conditions.…”
mentioning
confidence: 99%
“…Additionally, the advancements in the field of molecular biology and techniques have led to discovery of many new therapies, such as gene therapy, which has been widely applied to LDD clinical treatment. [ 19 , 20 ] The study found that compared with the control group, TSLP-positive expression was lower than that in the case group. The case group showed a higher TSLPR protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although CTGF could not directly stimulate the proportion of DNA in fibroblasts, it could raise the growth factor of fibroblasts, which further strengthens the effects of CTGF and other growth factors . The study of in vitro cell culture shows that TGF‐β could promote the rapid, significant, and lasting increase in CTGF …”
Section: Discussionmentioning
confidence: 99%